Macrophage stimulating protein preserves blood brain barrier integrity after intracerebral hemorrhage through recepteur d'origine nantais dependent GAB1/Src/β‐catenin pathway activation in a mouse model. Issue 1 (5th December 2018) - Lu, Tai; Wang, Zhong; Prativa, Sherchan; Xu, Yang; Wang, Tian; Zhang, Yiting; Yu, Lingyan; Xu, Ningbo; Tang, Jiping; You, Wanchun; Chen, Gang; Zhang, John H.
Abstract: Blood brain barrier (BBB) disruption is an important contributor to brain edema and neurological deficits following intracerebral hemorrhage (ICH). Macrophage stimulating protein (MSP) is a hepatocyte growth factor‐like protein that mediates its functions via activating receptor tyrosine kinase recepteur d'origine nantais (RON). Grb2‐associated binder 1 (GAB1) is a docking protein that mediates downstream receptor signal transduction pathways. This study aimed to evaluate the role of MSP and RON activated signaling pathway in preserving BBB integrity after collagenase‐induced ICH. ICH mice received recombinant human MSP (rhMSP) or rhMSP combined with siRNA knockdown of RON or GAB1. rhMSP was administered by intranasal route 1 h after ICH. Brain edema, neurobehavior, BBB tight junction protein expression, and BBB permeability were evaluated. The expression of endogenous MSP and p‐RON was decreased after ICH. Exogenous rhMSP administration reduced brain edema, neurological deficits, BBB permeability, and increased the expression of tight junction proteins in ICH mice. rhMSP administration increased the expression of p‐RON, p‐GAB1, p‐Src, nuclear β‐catenin, and tight junction proteins after ICH. These effects were reversed with RON and GAB1 siRNA. We conclude that MSP activation of RON preserved BBB integrity via GAB‐1/Src/β‐catenin pathway, thereby reducing brain edema and neurological deficits after ICH in mice. Abstract : Blood brain barrier (BBB) disruption is an important contributor to brain edema and neurological deficits following intracerebral hemorrhage. We propose the mechanism of macrophage stimulating protein mediated BBB protection. Macrophage stimulating protein is a hepatocyte growth factor‐like protein that mediates its function via activating receptor tyrosine kinase recepteurd'originnantais. This activation induces the phosphorylation of Grb2‐associated binder 1 and Src, then contributes to nuclear translocation of β‐catenin which increases the expression of tight junction proteins to alleviate BBB disruption after intracerebral hemorrhage. These findings may provide a new strategy for the treatment of intracerebral hemorrhage.